KAJIAN KRITIS TERHADAP LAPORAN KINERJA PERUSAHAAN DAN IMPLIKASINYA TERHADAP REPUTASI DAN KEPERCAYAANPUBLIK - Rifki Karta Surya; Ersi Sisdianto (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Corporate performance reports are a crucial tool for evaluating a company's operational and strategic efficacy in the eyes of stakeholders. These reports, however, frequently function as a tool for both informing and influencing public opinions regarding the company's credibility and trustworthiness. Examining the effects of corporate performance reports on public trust and reputation, as well as the consequences of the reports' quality and transparency, is the goal of this study. This study used literature reviews and content analysis of performance reports from a number of Indonesia's top companies as its methods. The study found that while dishonest reportsdamage a company's reputation and undermine public trust, truthful and transparent reports